Green potential rating tool: an assessment of green potential for conventional buildings - S.N.N. Syed Yahya,; A.R.M. Ariffin,; M.A. Ismail, (Penerbit UKM, 2014)
Assessment of the green potentials in a conventional building is rarely discussed in past literature unlike other types of assessments, such as a building’s current performance and qualities. ‘Green potential’ is the capacity of a conventional building to be refurbished into a green building. This paper presents the development of a rating tool to assess green potentials of existing conventional buildings. The development process involves reviewing relevant literature on the existing assessment tools. The review focuses on identifying methods and indicators that can be adopted for the assessment of green potentials. It is discovered that while literature on green potential assessment is limited, the frameworks of other types of assessments concerning green buildings are still suitable to be adopted. Additionally, with some modifications, commercial green building rating tools provide the most suitable indicators to assess green potentials. Apart from filling the knowledge gap, the tool developed may also assist building managers strategize towards achieving sustainability for large building stocks such as a small township or a university campus.